CUB Cafeteria a feasibility study for the UPV Employees Cooperative - Aponesto, Ma. Aileen; Camiña, Ma. Luvy; Deslate, Marivi; Gonzales, Rene Chito; Ong, Sonia; Panaguiton, Benmar B.; de Los Santos, Levi; Terencio, Andrelyn; Tupas, Laarni
Executive Summary-The UP VISAYAS Employees Cooperative was established in 1995 at Miag-ao, Iloilo. One of its objectives is to provide members with basic goods and services. Composed of UP Visayas employees, it presently has 298 members. In the later months of 1997, UP VISAYAS Administation offered the Cooperative an opportunity to manage the cafeteria services at the College Union Building (CUB). Private individuals who are renting the place for a monthly fee of about P9,000 then serviced the CUB cafeteria. Since it started operations, the cafeteria has experienced a second turnover of management with the latter management opting not to renew their contract. Instead of the monthly rent, the VISAYAS Administration will have a share in the profit of the dining service. As of this writing, the method of sharing was not yet agreed upon by the committee from the Administration and the Cooperative's Board of Directors. Management turnover was not due to the absence of demand for food service. The CUB cafeteria, located at the heart of the different colleges, the library and the administration building, has a big potential market for its services. The market study shows that it would be able to deliver the demand of that in the form of affordable and convenient food service. Though competition does exist, the cafeteria under the cooperative's management can overcome this through its delivery service and the various marketing schemes it will employ. Technically, the project will be using the existing facilities at CUB. Except for some acquisitions, minor repairs and installation of facilities, the place is ready for occupancy and operation. Raw materials of the operation of the project are readily available throughout the year. Supplies are abundant in Miag-ao and some can be availed on credit. When not available, these can be purchased in Iloilo City where some items, like groceries, are cheaper, widely available and can also be charged on a term account. The cafeteria has the capacity to procure and store these raw materials on a weekly basis. The over-all operation of the project will be under the management of the cooperative officers. However, the hired personnel from Miag-ao, Iloilo, will handle actual delivery of service. The compensation package will commensurate their qualifications and will be within the bounds of the labor code. With these hired personnel filling the organizational structure of the dining service, the cooperative could effectively and efficiently plan and schedule the project's smooth operation. The project would require about P300,000 to start its operations. This amount could be raised through member's contributions as well as from outside sources. Land Bank of the Philippines had started their interest and willingness to grant a loan to the cooperative at a low interest and without collateral. with the loan and the pledges, the cooperative could start the operations of the project at a minimum period of time. The financial projections made in the financial aspect of this study indicate a bright future for the cooperative. In its initial year, for a period of two months and a half, the forecasts already show positive results. The succeeding years also had the same outcome. In its operations, it is deemed liquid and has a high ownership leverage. These favorable forecasts are further ratified by the results of a capital investment analysis. The results describe a good project with a high rate of return and can be recovered wthin a short period of time. The operation of this cafeteria would benefit members of the cooperative, the UP Visayas constituents and the town of Misg-so, For the members, the cafeteria could provide source of livelihood aside from the yearly dividends. The cafeteria expects that members will, later on, be the suppliers of its raw materials. It would encourage them to venture to backyard gardening, poultry and hog raising and have the cafeteria as the buyer of their produce. This arrangement could also be anaother business opportunity for the cooperative for members can be provided with loans as capital and the cooperative eventually generating additional income in the form of interest. Economic benefits would also flow to the community of Miag-ao. Aside from employment opportunities offered to its residents, Miag-ao residents themselves will gain other incentives as suppliers of the cafeteria's raw materials. The cooperative, being a part nd parcel of the University, will avail of the free consultation services from other units of the University. Backed up by the Administration and composed of the UP VISAYAS constituency, the cooperative can save on other cost by utilizing the expertise of the various units of the University in the effective and efficient management and operation of its dining services. In exchange for that, te cafeteria, and the cooperative, will serve as a training ground for the University students. As a sort of laboratory, the students could experience the different theories and principles in the fields of management, accounting, marketing and food processing come to work. The Cooperative is expected to commence its operation on October 1998.